(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2025)
Bread production often involves the addition of potassium bromate to enhance product quality. The study analyzed potassium bromate levels in bread brands from Mwanza and Kagera regions, Tanzania. This analysis was conducted due to the carcinogenic risks associated with potassium bromate when it exceeds the US-FDA’s permissible concentration of 0.02 mg/kg. Twenty-one bread samples were randomly collected from the study areas and analyzed for potassium bromate content using David Pearson’s qualitative and quantitative methods at the Tanzania Bureau of Standards laboratories. The results obtained showed that all samples contained potassium bromate, with concentrations ranging from 1.02 - 4.85 μg/g, which is significantly above the permissible limit. Consequently, all brands tested are unsafe for human consumption due to excessive bromate levels. This indicates a significant public health risk and underscores the need for stricter regulatory enforcement to ensure adherence to food safety standards.